Pengaruh Viralitas Meme Marketing, Brand Image, dan Brand Personality terhadap Brand Engagement dan Loyalitas Konsumen - Putri, Firly Marshanda; Salqaura, Siti Alhamra; Lubis, Adelina (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to investigate how brand engagement and customer loyalty toward smartphone products among Generation Z in Medan are influenced by Meme Marketing Virality, Brand Image, and Brand Personality. An associative and quantitative approach was employed, using purposive sampling to select a total of 220 respondents. Data were collected through an online survey via Google Forms and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the SmartPLS 4 software. The findings reveal that: (1) Meme Marketing Virality has a positive and significant effect on Brand Engagement (β = 0.182; t = 3.783; p = 0.000), but a negative and significant effect on Customer Loyalty (β = -0.125; t = 2.838; p = 0.005); (2) Brand Image has a positive and significant effect only on Customer Loyalty (β = 0.282; t = 2.097; p = 0.036), but not on Brand Engagement (β = 0.023; t = 0.095; p = 0.924); (3) Brand Personality has a positive and significant effect on both Brand Engagement (β = 0.708; t = 3.962; p = 0.000) and Customer Loyalty (β = 0.305; t = 2.612; p = 0.009); and (4) Brand Engagement positively and significantly affects Customer Loyalty (β = 0.422; t = 4.009; p = 0.000).